Incidence Rate and Risk Factors for Diarrhea in Yarsi Medical Faculty Students Batch 2019 - Izzatul Eryando; Ike Irmawati; Endy Muhammad Istiwara (Junior Medical Journal, 2023)
Introduction: Diarrhea is a bowel movement with a mushy or liquid consistency, which can even be water only with a frequency more often than usual (usually three or more times) in one day (Depkes RI 2011). The prevalence of diarrhea in Indonesia according to its characteristics based on the 2018 Riskesdas recorded 18,225 (9%) children with diarrhea aged 1 year, 73,188 (11.5%) children with diarrhea aged 1-4 years, 182,338 (6.2%) children with diarrhea aged 5-14 years, and 165,644 (6.7%) children with diarrhea aged 15-24 years (Ministry of Health, 2019). Diarrhea can occur due to factors such as open defecation, hand washing without soap, food and beverage management, waste safety, and liquid waste safety.Methodology: This study is a correlational study with a cross sectional design. The study population was YARSI medical students. The sampling technique was purposive sampling. The total sample was 166 students.Results: In student respondents, the results showed that the incidence rate of diarrhea in medical students of Yarsi in the last 3 months was quite high because the majority had diarrhea. It is also known that several risk factors studied have a relationship with the incidence rate of diarrhea, namely hand washing behavior and also the source of water drunk. Meanwhile, the level of knowledge, gender, and location of food purchases are not related to the incidence of diarrhea in students.Conclusion: The results of the study found the prevalence of diarrhea and several risk factors associated with the incidence of diarrhea.